2010
DOI: 10.1364/oe.18.017521
|View full text |Cite
|
Sign up to set email alerts
|

Wavefront aberration measurements and corrections through thick tissue using fluorescent microsphere reference beacons

Abstract: We present a new method to directly measure and correct the aberrations introduced when imaging through thick biological tissue. A Shack-Hartmann wavefront sensor is used to directly measure the wavefront error induced by a Drosophila embryo. The wavefront measurements are taken by seeding the embryo with fluorescent microspheres used as “artificial guide-stars.” The wavefront error is corrected in ten millisecond steps by applying the inverse to the wavefront error on a micro-electro-mechanical deformable mir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 19 publications
0
52
0
Order By: Relevance
“…By approximating the solution of Eq. (12), these algorithms use the additional N measurements to estimate all the eigenvalues of Q each time the aberration correction is applied (see Section 4 in [26]). Nevertheless, variations in the orientations of the eigenvectors, such as the ones detected during our experiments, are not accounted for and affect the accuracy of the aberration correction (see Section 3 in [34]).…”
Section: H Variations Of the Parameters Over The Field Of Viewmentioning
confidence: 99%
See 1 more Smart Citation
“…By approximating the solution of Eq. (12), these algorithms use the additional N measurements to estimate all the eigenvalues of Q each time the aberration correction is applied (see Section 4 in [26]). Nevertheless, variations in the orientations of the eigenvectors, such as the ones detected during our experiments, are not accounted for and affect the accuracy of the aberration correction (see Section 3 in [34]).…”
Section: H Variations Of the Parameters Over The Field Of Viewmentioning
confidence: 99%
“…Additionally, these measurements are weakly sensitive to odd aberrations [5], due to the double-pass effect [11]. In another solution, instead, the emission from a point source inside the specimen is used to perform ShackHartmann wavefront sensing [12][13][14][15][16]. Here, the difficulty stems from the lack of such reference point sources within the specimen and from the limited number of photons available in the emission signal.…”
Section: Introductionmentioning
confidence: 99%
“…One class of methods are sensorless methods [10][11][12][13][14] that iteratively optimise a metric such as the mean intensity or sharpness based on the fluorescence signal, without using a dedicated wavefront sensor. Alternatively, the fluorescence can be used to measure the wavefront directly, either using fluorescent beads [15,16], or fluorescent proteins [17][18][19][20] as the biological equivalent of astronomical guide stars [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Azucena et al 18 have successfully demonstrated the ability of a S-H/DM loop to measure and correct the wavefront from fluorescent beacons injected in a drosophila embryo.…”
Section: Introductionmentioning
confidence: 99%